External Quality Assessment of 24, 25-dihydroxyvitamin D3 (24, 25(OH)2D3) assays. Issue 187 (March 2019) - Carter, G.D.; Ahmed, F.; Berry, J.; Cavalier, E.; Durazo-Arvizu, R.; Gunter, E.; Jones, G.; Jones, J.; Phinney, K.; Sempos, C.T.; Twomey, P.J.; Williams, E.L.; et al.
Highlights: DEQAS is an accuracy-based External Quality Assessment Scheme EQA) for 25-OHD and is running a pilot EQA scheme for 24, 25(OH)2 D3 . Serum 24, 25(OH)2D3 is highly correlated with 25-OHD3 . Results submitted to DEQAS show high variability among laboratories measuring 24, 25(OH)2 D3 . It is suggested that differences in assay standardization and/or poor assay sensitivity may influence high inter-laboratory imprecision. The National Institute for Standards and Technology (NIST) have produced human serum-based Standard Reference Materials (SRMs) and a high concentration ethanol-based SRM for calibrating 24, 25(OH)2 D3 standards. DEQAS will continue to run an External Quality Assessment Scheme (EQA) for 24, 25(OH)2 D3 . Abstract: The discovery that mutations of the CYP24A1 gene are a cause of idiopathic infantile hypercalcemia (IIH) has revived interest in measuring serum 24, 25(OH)2 D3 . Several studies have also suggested that a high 25-hydroxyvitamin D3 (25-OHD3 ):24, 25(OH)2 D3 ratio might provide additional diagnostic information in the investigation of vitamin D deficiency. Measurement of 24, 25(OH)2 D3 is necessarily restricted to laboratories with mass spectrometry methods although cross reactivity of the metabolite in immunoassays for 25-OHD is a potential cause of misleading results. The international External Quality Assessment (EQA) scheme for vitamin D metabolites (DEQAS) was set up in 1989. In 2013 DEQAS became an accuracy based EQA for 25-OHD with 'target values' assigned by the National Institute of Standards and Technology (NIST) Reference Measurement Procedure (RMP). A pilot scheme for serum 24, 25(OH)2 D3 was started in 2015 and participants were asked to measure the metabolite on each of the 5 samples sent out for 25-OHD. Inter-laboratory agreement was poor but this may reflect methodological differences, in particular different approaches to assay standardization. An important potential contribution to reducing variability among assays was the development by NIST of a 24, 25(OH)2 D3 RMP and its use in assigning values to SRMs 972a, 2973 and 2971, supported by the NIH Office of Dietary Supplements (ODS) as part of the Vitamin D Standardization Program (VDSP) effort.